Kajian Etika Keilmuan dalam Filsafat Sains - Inas Aulia Majid; Andri Gunawan Junaedy; Sutarno Sutarno; I Ketut Mahardika (Jurnal Ilmiah Wahana Pendidikan, 2023)
In essence, humans will always try to improve and develop their knowledge to fulfill self-satisfaction, the demands of the times and seek the truth. Learning everything with knowledge is basically an effort made by humans to get to the truth. Truth is the conformity between the object of study and the actual object, thus studying something through philosophy is a step towards obtaining true and objective knowledge. Science that has developed and has an impact on humans can cause a shift in problems from the material aspect to the mental aspect. The rapid development of modern science and technology tends not to pay attention to aspects of the value system, both ethical and religious values, resulting in human moral degradation. This study aims to determine the importance of the study of scientific ethics in the philosophy of science. Philosophy of science is used to study, reveal, and solve scientific problems for human life through relevant scientific methods. By literacy study methods, this study discusses the nature of philosophy, the nature of science, the relationship between ethics and science and the importance of ethics in the development of science.